Evaluation of prenatal care quality in a baby-friendly hospital in the brazilian northeast interior (Research, Society and Development, 2022)
Prenatal care presents a set of measures aimed at ensuring that healthy newborns are delivered without causing harm to women's health. Including health promotion and prevention, as well as proper diagnosis and treatment of difficulties that may arise. The current study aims to analyze the epidemiological profile of pregnant women who gave birth at a Baby-Friendly Hospital in the interior of Sergipe state, in the years 2018 and 2019, and to determine the quality of prenatal care for the population involved. This research is an epidemiological, retrospective, and cross-sectional analytical study based on data collected from the Sinasc database on the Datasus platform. The findings revealed a high coverage of prenatal care with more than 90% of pregnant women at term birth starting prenatal care before the 16th gestational week (98.1%; n = 2,972). According to the Ministry of Health's recommended number of consultations, 97.3 percent of pregnant women who delivered at full term (n = 2947) received at least six consultations. Regarding age, pregnant women over 20 years old accounted for more than 75% of children with adequate birth weight (between 2500 and 3999 g). Multipara, no previous cesarean, single pregnancy, cephalic baby, spontaneous labor were the most frequent Robson classifications. As has been noted, the Itabaiana municipality's Baby-Friendly Hospital has a high rate of prenatal care coverage; nonetheless, there are issues with the hospital's adequacy for the Prenatal and Birth Humanization Program.